The EFEKTIVITAS ANTIBAKTERI MENGANDUNG JINTAN HITAM (Nigella sativa L.) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus SEBAGAI PEMBERSIH GIGI TIRUAN - Dharma Satya; Asha Mustika Putri; Dewi Nurul Mustaqimah; Siti Nur Riani (Lembaga Penelitian Universitas YARSI, 2025)
Introduction: Black cumin (Nigella sativa L.) is a miraculous and multifunctional herbal plant that has the potential to treat various diseases since the time of the Prophet Muhammad. One of the potential concerns of the scientific community is the antibacterial effect of black cumin extract. This is due to the content of its main active substance, thymoquinone. Black cumin is safe for consumption, easily available, and harmless to the environment. Objective: This study aims to determine the antibacterial effectiveness of black cumin-containing solution and black cumin oil-containing emulsion, and its function as a denture cleaner. Research Methods: This study was a laboratory experimental study. Using disc diffusion method for antibacterial test. This study used solutions containing black cumin and emulsions containing black cumin oil with concentrations of 10%, 20%, 30%, 40%, 50%, alkaline peroxide solution, sodium perborate solution, and distilled water. The total samples used were 48 samples with 3 repetitions in each group. Results: The results of the One Way Anova test showed that there was a significant effect on the solution against S. aureus bacteria and a significant difference between each concentration (p <0.05). Conclusion: The solution containing 50% black cumin was found to have better antibacterial effectiveness with an average inhibition zone diameter of 11.08 mm compared to the emulsion containing 50% black cumin oil which only had an average inhibition zone diameter of 2.61 mm.